Antitumor activity of paederosidic acid in human non-small cell lung cancer cells via inducing mitochondria-mediated apoptosis. (1st May 2017) - Yu, Ping; Shi, Lifeng; Song, Meiyan; Meng, Yu
Abstract: This study was aimed to investigate antitumor activity of paederosidic acid (PA) in human non-small cell lung cancer cells and explore the related mechanisms. The anti-proliferative effects of PA on A549 cells were evaluated by MTT method and the IC50 values were calculated. Furthermore, the PA-induced apoptosis in A549 cells was determined by fluorescence microscope via staining with DAPI and by flow cytometer via staining with FITC conjugated Annexin V/PI. The expression of apoptosis-related or signaling proteins was investigated by Western blotting. Our results demonstrated that PA showed significant anti-tumor activity on lung cancer in vitro ; the mechanisms were involved in inducing mitochondria-mediated apoptosis via up-regulation of caspase-3, caspase-8, caspase-9, Bid, Bax, down-regulation of Bcl-2 and stimulating the release of Cyto-C from mitochondria. In addition, JNK phosphorylation levels significantly increased concomitantly with decrease in Akt phosphorylation after treatment with PA in A549 cells. However, JNK siRNA-transfected cells diminished PA-induced caspase-3, 8 and 9, Bid and Bax activaton while enhanced the Bcl-2 activation. Collectively, these results indicated that PA-induced JNK activation played an important functional role in apoptosis. Highlights: Paederosidic acid inhibited human non-small cell lung cancer cells growth. Paederosidic acid induced A549 cells apoptosis. The pro-apoptosis effect might be mediated by promoting the release of Cyoto-C from mitochondria, upregulating caspase-3, caspase-8, caspase-9, Bid, Bax, P-JNK, and down-regulating Bcl-2, p-Akt.